Stability Analysis upon High-Pressure Common Rail Fuel Injection System under Multiple Injection Modes - Lan, Qi; Bai, Yun; Ma, Xiuzhen; Fan, Liyun; Xu, Jing (International journal of automotive technology, 2021)
Fuel injection stability of high-pressure common rail fuel injection system (HPCRFIS) under multiple injection modes is a recognized technical problem. To explain it essentially, a numerical model based on bond graph method, which provides a standardized series of symbol system to describe various components in different physical fields as well as interactive effect analysis tool for different energy categories, was used to investigate the problem. As HPCRFIS is a typical nonlinear system with multi-physical coupling, it is very difficult to analyze system stability directly. Therefore, the system was linearized at typical moments. The system matrix for each typical moment was obtained thereby. To investigate the influential mechanism of system stability deeply, the variations of rank and eigenvalues distributions of state matrices were analyzed. The results show that the rank of state matrices changes abruptly when the needle or control valve moves. In terms of system stability, the oscillation characteristics are subject to the movement of needle or control valve. The ending of the former injection causes the system to show damping oscillation characteristics before the latter injection starts. The motion of control valve makes more contribution to system stability than that of needle, which could be concluded by Lyapunov stability criterion.